"Ship‐in‐a‐Bottle" Strategy for Immobilization of 9‐Amino(9‐deoxy)epi‐Cinchona Alkaloid into Molecularly Imprinted Solid Acid: Acetal Hydrolysis/Asymmetric Aldol Tandem Reaction. Issue 2 (19th November 2020) - Wei, Shuai; Zhang, Jianing; Li, Shan; Ma, Xuebing
Abstract: Direct immobilization of versatile 9‐amino(9‐deoxy) epi ‐cinchona alkaloids without molecule modification to achieve heterogeneous organocatalysis is of interest in the low‐cost production of optically active compounds. In this paper, an exquisite "ship‐in‐a‐bottle" strategy for direct and simple immobilization of 9‐amino‐(9‐deoxy) epi ‐quinine (QNNH2 ) into hollo w polystyrene nano‐bowl with imprinted free space around −SO3 H was developed via acid‐base reaction and radical polymerization. The heterogeneous organocatalyst with 0.44 mmol g −1 of QNNH2 and 0.48 mmol g −1 of residual −SO3 H possessed fast mass transfer due to the characteristic architectural features, such as thin shell thickness, free space around catalytic site, and hollow interior. In heterogeneous acetal hydrolysis/asymmetric aldol tandem reaction, good to excellent catalytic performances (90–95 % yields, anti/syn =88/12–96/4, and 97–99 % ee anti ) for acetals bearing electron‐withdrawing substituents (R= o, m, p‐ NO2, Cl) were achieved. The "ship‐in‐a‐bottle" QNNH2 displayed good stability and reusability with excellent catalytic performances in the reuses. Abstract : "Ship‐in‐a‐bottle" strategy for the direct immobilization of 9‐amino(9‐deoxy) epi ‐cinchona alkaloid into molecularly imprinted hollow solid acid without molecular modification was developed via simple acid‐base reaction and radical polymerization. Good to excellent catalytic performances, including yield and stereoselectivity, were achieved in heterogeneous acetal hydrolysis/ asymmetric aldol tandem reaction due to its hollow and mesoporous characteristic architectural features.